(2xy-y)(2xy-y)=

Simple and best practice solution for (2xy-y)(2xy-y)= equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for (2xy-y)(2xy-y)= equation:


Simplifying
(2xy + -1y)(2xy + -1y) = 0

Multiply (2xy + -1y) * (2xy + -1y)
(2xy * (2xy + -1y) + -1y * (2xy + -1y)) = 0
((2xy * 2xy + -1y * 2xy) + -1y * (2xy + -1y)) = 0

Reorder the terms:
((-2xy2 + 4x2y2) + -1y * (2xy + -1y)) = 0
((-2xy2 + 4x2y2) + -1y * (2xy + -1y)) = 0
(-2xy2 + 4x2y2 + (2xy * -1y + -1y * -1y)) = 0
(-2xy2 + 4x2y2 + (-2xy2 + 1y2)) = 0

Reorder the terms:
(-2xy2 + -2xy2 + 4x2y2 + 1y2) = 0

Combine like terms: -2xy2 + -2xy2 = -4xy2
(-4xy2 + 4x2y2 + 1y2) = 0

Solving
-4xy2 + 4x2y2 + 1y2 = 0

Solving for variable 'x'.

Factor out the Greatest Common Factor (GCF), 'y2'.
y2(-4x + 4x2 + 1) = 0

Factor a trinomial.
y2((2x + -1)(2x + -1)) = 0

Subproblem 1

Set the factor 'y2' equal to zero and attempt to solve: Simplifying y2 = 0 Solving y2 = 0 Move all terms containing x to the left, all other terms to the right. Add '-1y2' to each side of the equation. y2 + -1y2 = 0 + -1y2 Remove the zero: 0 = -1y2 Simplifying 0 = -1y2 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.

Subproblem 2

Set the factor '(2x + -1)' equal to zero and attempt to solve: Simplifying 2x + -1 = 0 Reorder the terms: -1 + 2x = 0 Solving -1 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 2x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 2x = 0 + 1 2x = 0 + 1 Combine like terms: 0 + 1 = 1 2x = 1 Divide each side by '2'. x = 0.5 Simplifying x = 0.5

Subproblem 3

Set the factor '(2x + -1)' equal to zero and attempt to solve: Simplifying 2x + -1 = 0 Reorder the terms: -1 + 2x = 0 Solving -1 + 2x = 0 Move all terms containing x to the left, all other terms to the right. Add '1' to each side of the equation. -1 + 1 + 2x = 0 + 1 Combine like terms: -1 + 1 = 0 0 + 2x = 0 + 1 2x = 0 + 1 Combine like terms: 0 + 1 = 1 2x = 1 Divide each side by '2'. x = 0.5 Simplifying x = 0.5

Solution

x = {0.5, 0.5}

See similar equations:

| 46q-34=54q-82 | | 1/4x+3=17 | | (n/8)-3=-11 | | -7(1+7r)-6=379 | | s^2+8s-9=0 | | 125m-75m+43875=46125-175m | | 2x+3(-8)=0 | | 15x-2.4x=0.6+7.6x | | -4(x)-2y=-12 | | 25p^2-4=0 | | 5x=40*0.5 | | a=h(b+c)solve(b) | | 2x+5(x-1)= | | 3(-11)[5(-3)-7(-2)]= | | 6xrqw+13xrqw=133 | | 9s-36=5s | | 64g^3-125h^3=0 | | 13(x-4)=8x-32 | | 16t^2=-h+100 | | 3/4+1/4x=3/4x-1/4 | | -4=3n-7n | | 2x-60=x | | x-2=14*2 | | 16t^2+h=100 | | 1-11-3x=32 | | x+by=c*x | | (2m-7)squared= | | 2(7)-2x=6 | | 12x-4(3x)=0 | | 4b-8b^2=0 | | x/2-1/5=x/3+1/4 | | Y+5/8=-2 |

Equations solver categories